Issues in news and reporting selections from CQ Researcher. - McCutcheon, Chuck 1963- (Thousand Oaks, California CQ Press, an imprint of SAGE Publications, Inc., 2019)
"Written by award-winning CQ Researcher journalists, this collection of non-partisan reports focuses on 11 hot-button issues facing journalists and news organizations. With reports ranging from perceptions of media bias and threats to free speech, Issues in News and Reporting promotes in-depth discussion, facilitates further research, and helps readers formulate their own positions on crucial issues. ... The reports are expertly researched and written, presenting readers with all sides of an issue"--Back cover.
Includes bibliographical references.
Keywords: Journalism -- United States; Reporters and reporting -- United States; Mass media -- Objectivity -- United States; Freedom of speech -- United States; Freedom of the press -- United States